USING METACOGNITIVE SKILLS IN LEARNING CHEMISTRY THROUGH PROBLEM SOLVING - Syahmani - (PROSIDING SEMINAR KIMIA, 2015)
Have been done study about using metacognitive skills in learning chemistry through problem solving. Metacognitionis the awareness of cognitive processes. By using metacognition, someone does all the activities with full awareness. When students learning chemistry by involving their metacognitive skills, students will be able to observe the relationship between data in the problem with the prior knowledge, to re-examine its accuracy, as well as solving acomplex problem with the simple steps, tries to regulate and improve their cognitive processes. This paper aims is prepared in order to build a mindset learning chemistry through problem solving that involve students metacognitive skills. Metacognitive skills to form a competent student resources, who perform all acts by full awareness. Always make good representing problem, planning, monitoring, evaluating, and transfering their action. The i-SMART model helps students to solve problems in a systematical way and supported scaf folding metacognitive questioning. So, metacognitive support during the solution process in problem solving chemistry more effective..